Flexibility in international dispute settlement : conciliation revisited - Tomuschat, Christian; Kohen, Marcelo G. (Brill Nijhoff, 2020)
"In recent years, the tendency has been to settle international disputes by informal methods. Among those methods conciliation has seen a successful revival, after many years of decline, in the case of Timor Leste v. Australia while inter-State complaint proceedings under the UN-sponsored human rights treaties have unexpectedly reached their merits stage of conciliation. The present book takes stock of these developments by portraying, at the same time, the potential of the OSCE Court of Conciliation and Arbitration which still remains to be fully activated. Additionally, the contributions reach out to geographical areas in Africa and Asia. An analysis of the relevant procedural mechanisms completes the study to which 14 authors from nine different countries have contributed"--